Association of mitochondrial DNA displacement loop polymorphisms and aggressive periodontitis in a Chinese population: a pilot study. (June 2015) - Wang, Xiaoxuan; Guo, Yuan; Luan, Qingxian
Abstract To examine whether certain mitochondrial DNA (mtDNA) haplogroups and/or alterations affect susceptibility to aggressive periodontitis (AgP), we analyzed the mtDNA D-Loop region in a Han Chinese population. The mtDNA haplogroups were analyzed in 58 patients with AgP and 50 periodontally healthy controls. The frequency of haplogroups A in AgP group was significantly higher than that in the control group (p = 0.007). Furthermore, the frequency of haplogroup D was higher in the control group than that in AgP group (p = 0.007). The frequencies of D-Loop polymorphisms m.16126T > C, m.16290C > T and m.152 T > C were significantly higher in patients with AgP compared with controls (p = 0.029, 0.014 and 0.022, respectively). Additionally, the frequencies of three other D-Loop polymorphisms, m.16223C > T m.489 T > C and m.515CA deletion (del) were significantly lower in patients with AgP compared with controls (p = 0.042, 0.003 and 0.026, respectively). Our study showed for the first time, an association between AgP and mtDNA haplogroups. Haplogroups A was implicated as a risk factor for AgP, while haplogroups D exhibited a protective effect in this disease. These observations may provide a new perspective on the study of the pathogenesis of periodontitis.